2015
DOI: 10.1016/j.jmmm.2014.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the high temperature superconducting cuprates from resonant inelastic X-ray scattering

Abstract: Recent improvements in instrumentation have established resonant inelastic x-ray scattering (RIXS) as a valuable new probe of the magnetic excitations in the cuprates. This article introduces RIXS, focusing on the Cu L 3 resonance, and reviews recent experiments using this technique. These are discussed in light of other experimental probes such as inelastic neutron scattering and Raman scattering. The success of these studies has motivated the development of several new RIXS spectrometers at synchrotrons arou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 126 publications
(243 reference statements)
3
70
0
Order By: Relevance
“…Data were collected using a Fast CCD [52] with a maximum readout rate of 100 Hz and 30×30 µm 2 pixel size placed 340 mm from the sample. Single crystals of LBCO 1/8 were grown using the floating zone method, and characterized extensively in previous studies [41,43,44,53]. Here we report wavevectors in terms of the HTT crystal structure with a = b = 3.78 and c = 13.28Å.…”
Section: Flux (∼ 10mentioning
confidence: 99%
“…Data were collected using a Fast CCD [52] with a maximum readout rate of 100 Hz and 30×30 µm 2 pixel size placed 340 mm from the sample. Single crystals of LBCO 1/8 were grown using the floating zone method, and characterized extensively in previous studies [41,43,44,53]. Here we report wavevectors in terms of the HTT crystal structure with a = b = 3.78 and c = 13.28Å.…”
Section: Flux (∼ 10mentioning
confidence: 99%
“…Such a large energy scale would naturally be expected to play a central role over a large fraction of the phase diagram. There have consequently been extensive efforts to characterize the nature of magnetism across the cuprate phase diagram [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], which have demonstrated that substantial magnetic spectral weight persists to at least optimal doping (i.e. a hole concentration x ≈ 0.15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RIXS has been used to successfully detect high energy magnetic excitations in superconducting cuprates [8][9][10][11][12][13][14] and FePns 15 . Moreover, INS and RIXS techniques complement each other in their span of the reciprocal space, with RIXS probing around the Γ point and INS measuring around the antiferromagnetic ordering vector point in the Brillouin zone 4,5,16,17 .…”
Section: Introductionmentioning
confidence: 99%